Islatravir for the treatment and prevention of infection with the human immunodeficiency virus type 1. Issue 1 (January 2020) - Markowitz, Martin; Grobler, Jay A.
Abstract : Purpose of review: To discuss the potential role of islatravir (ISL), a novel reverse transcriptase translocation inhibitor, in the treatment and prevention of human immunodeficiency virus type 1 (HIV-1) infection. Recent findings: Islatravir (4′-ethynyl-2-fluoro-2′-deoxyadenosine, MK-8591) is a long-acting first-in-class nucleoside reverse transcriptase translocation inhibitor with the potential for versatile dosing routes and dosing intervals. It demonstrated robust antiviral activity when dosed once daily and once weekly in HIV-1-infected individuals and SIV-infected rhesus macaques. In clinical trials of ISL in combination with doravirine and lamivudine, daily oral administration resulted in high levels of virologic suppression in HIV-infected individuals. In preclinical studies, ISL dosed orally once-weekly as preexposure prophylaxis (PrEP), protected rhesus macaques against SHIV infection via the mucosal route in the low-dose rectal challenge model. Most recently, data in healthy HIV-1-uninfected individuals demonstrated the feasibility of formulating of ISL as an implant. In these studies, levels of intracellular ISL-triphosphate were consistent with the potential for a once-yearly implantable administration of ISL as PrEP. Summary: Islatravir is a promising new agent for both the treatment and prevention of HIV-1 infection.